2017
DOI: 10.1002/alr.21996
|View full text |Cite
|
Sign up to set email alerts
|

Significance of human papillomavirus positivity in sinonasal squamous cell carcinoma

Abstract: HPV positivity is more common in nasal cavity SCC and nonkeratinizing SNSCC. It is also a favorable prognostic factor in SNSCC. Future studies on SNSCC should take HPV positivity into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 46 publications
0
52
1
Order By: Relevance
“…In the past, sinonasal SCC has been linked to cigarette smoking and occupational exposures [ 7 ]. However, in recent years, the generational changes in sexual behavior may have led to an increased positivity rate for human papillomavirus (HPV) among patients with sinonasal SCC; consequently, HPV has been identified in 32–62% of all sinonasal SCCs [ 8 , 9 ]. HPV positivity is more common in SCCs of the nasal cavity than in paranasal SCCs [ 9 ].…”
Section: Sinonasal Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, sinonasal SCC has been linked to cigarette smoking and occupational exposures [ 7 ]. However, in recent years, the generational changes in sexual behavior may have led to an increased positivity rate for human papillomavirus (HPV) among patients with sinonasal SCC; consequently, HPV has been identified in 32–62% of all sinonasal SCCs [ 8 , 9 ]. HPV positivity is more common in SCCs of the nasal cavity than in paranasal SCCs [ 9 ].…”
Section: Sinonasal Malignanciesmentioning
confidence: 99%
“…However, in recent years, the generational changes in sexual behavior may have led to an increased positivity rate for human papillomavirus (HPV) among patients with sinonasal SCC; consequently, HPV has been identified in 32–62% of all sinonasal SCCs [ 8 , 9 ]. HPV positivity is more common in SCCs of the nasal cavity than in paranasal SCCs [ 9 ]. As with oropharyngeal SCCs, patients with a HPV-positive sinonasal SCC have a better prognosis than patients with a HPV-negative sinonasal SCC [ 8 , 9 ].…”
Section: Sinonasal Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Although the prognostic implications of HPV infection in SNSCC have not been fully elucidated, recent data suggest that HPV-associated SNSCC is more common in younger patients, occurs more often in the nasal cavity (as opposed to the paranasal sinuses), and is associated with better overall survival compared with HPVnegative tumors. 18,21,22 Morphologically, nonkeratinizing SNSCC is similar to nonkeratinizing squamous cell carcino- Figure 4. Benign entities in the differential diagnosis of sinonasal papillomas.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…A prior institutional report demonstrated an apparent improved survival rate in human papillomavirus (HPV)‐positive sinonasal squamous cell carcinomas (SN‐SCCs), similar to what is seen in other head and neck cancers . The Rutgers group queried The National Cancer Database and demonstrated that and of 770 SN‐SCC cases identified, 244 (31.7%) were HPV‐positive. HPV positivity was more common in nasal cavity tumors than in sinus tumors, and was indeed associated with improved overall survival.…”
mentioning
confidence: 94%